2020
DOI: 10.1186/s13018-020-01736-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of symmetrical restoration for the migration of uncemented total hip arthroplasty: a randomized RSA study with 75 patients and 5-year follow-up

Abstract: Background: Inferior placement of a femoral stem is predictive for early loosening and failure, but does restoration of the original hip anatomy benefit the function and survival of a total hip replacement? Methods: Seventy-five patients with primary unilateral hip osteoarthritis operated with an uncemented anatomical stem were randomized for either standard or modular stems. We used 50 ABG II stems with modular necks and 25 standard stems (control group). We measured the symmetry in hip anatomy between health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…The increased modification possibilities of modular stems with different neck options have previously been claimed as valuable for ROM, soft tissue balance, and to minimize leg length discrepancies (Barrack 1994, Jones 2004, Archibeck et al 2011, Srinivasan et al 2012. The RSA stem migration data showed that the ABG II proximal fit stem, in both the modular and non-modular version, is stable in its resting position after an initial slight subsidence and retroversion within the 3 first postoperative months (Kiernan et al 2020). There have, however, also been reports on disadvantages related to the additional neck-stem interface when using modular stems.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The increased modification possibilities of modular stems with different neck options have previously been claimed as valuable for ROM, soft tissue balance, and to minimize leg length discrepancies (Barrack 1994, Jones 2004, Archibeck et al 2011, Srinivasan et al 2012. The RSA stem migration data showed that the ABG II proximal fit stem, in both the modular and non-modular version, is stable in its resting position after an initial slight subsidence and retroversion within the 3 first postoperative months (Kiernan et al 2020). There have, however, also been reports on disadvantages related to the additional neck-stem interface when using modular stems.…”
Section: Discussionmentioning
confidence: 97%
“…Of the 75 stems that we had in our cohort for the former ABG II study (Kiernan et al. 2020 ), we were able to include 47 modular stems with sufficient RSA data during the follow-up period and 25 non-modular standard stems (up to 5 years’ follow-up). We lost 1 patient to follow-up due to an early periprosthetic femoral fracture (PPFF); we excluded 2 because of problems in performing the postoperative RSA examination ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The current cohort was based on a clinical study, reported elsewhere. 29 In that study, 75 patients were recruited for THA after informed consent and operated with the uncemented ABG II prosthesis (Stryker Orthopedics, Mahwah, NJ, USA). Due to incomplete imaging for various reasons, there were missing data for two patients preoperatively and two other patients postoperatively.…”
Section: Methodsmentioning
confidence: 99%